Diagnóstico multidimensional da sustentabilidade em agroecossistemas do Brasil e de Portugal - Lima, Andréia Santos de (2017)
The main objective of this research is to apply and analyze the agroecosystems sustainability by using the tool which facilitates the multidimensional evaluation of the sustainability degree in different agroecosystems, in the realities of Northeast in Brazil and the mountain region of Trás-os-Montes and Alto-Douro in Portugal. Through the application of this tool, the sustainability degree analysis of the studied agroecosystems was sought, using criteria that approach four important dimensions in the evaluation of sustainability: environmental, social, economic and agricultural. After applying the technique in field, the scores attributed to the several indicators systematized in this work were tabulated in spreadsheets in Microsoft Office Excel software. The averages of these scores were submitted to mathematical treatment and subsequently plotted on a radar chart. This mathematical tool allowed to express and demonstrate, in diferente shapes of geometrical patterns, the behavior of the scores attributed to the indicators of each dimension, in each studied agroecosystem. Thus, the radar charts allow to evaluate the agroecosystem sustainability, making it possible to discuss the studied dimensions and the indicators that compose each dimension, and, on the other hand, to gauge what prevents the achievement of sustainability. In Brazil, the systems of diversified production in agroecological transition (A1), based on agroforestry production, showed a higher level of sustainability when compared to the polyculture systems (A3) with low or zero levels of sustainability based on convencional cultivation (A2). Among the agroecosystems evaluated in Portugal, those that practice organic production with conventional practice predominance stand out, as they have the highest averages in the environmental and economic dimensions, followed by agriculture and, in a lesser degree of sustainability, the social dimension. The proposed tool presents technical viability to the evaluation of sustainability, involves the participation of people in the processes of building knowledge and also allows the identification of problems for taking solutions. The multidimensional evaluation tool studied is useful to analyze the degree of sustainability of the agroecosystems in the tropical reality of Northeast in Brazil and in the temperate region of Trás-os-Montes in Portugal.